2021
DOI: 10.1097/ju.0000000000002136
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculation Disorders in Male Patients with Cancer: A Systematic Review and Meta-Analysis of Prevalence

Abstract: Purpose: Ejaculatory dysfunction (EjD) and erectile dysfunction after cancer treatment are clinically important complications, but their exact prevalence by various kinds of cancer site and type of treatment is unknown. The aim of this systematic review and meta-analysis was to examine the available evidence and provide pooled estimates for prevalence of EjD and erectile dysfunction in relation to all cancer sites and identify characteristics associated with EjD in cancer patients. Materials and Methods: We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…In our study age was confirmed to be an independent predictor of sampling. Several analyses showed a high prevalence of ejaculatory dysfunction among patients with cancer and cancer survivors [23]. In our series, we found that 60% of men who had accepted to participate and were not able to collect their SF reported a psychogenic inhibition; all our patients had received a diagnosis of PCa.…”
Section: Discussionmentioning
confidence: 50%
“…In our study age was confirmed to be an independent predictor of sampling. Several analyses showed a high prevalence of ejaculatory dysfunction among patients with cancer and cancer survivors [23]. In our series, we found that 60% of men who had accepted to participate and were not able to collect their SF reported a psychogenic inhibition; all our patients had received a diagnosis of PCa.…”
Section: Discussionmentioning
confidence: 50%
“…Particularly, although our review identified two maternal-paternal outcomes (need for fertility treatment and birth rate), we did not identify any studies that specifically evaluated the impact of male AYA cancer on paternal reproductive health outcomes. A 2021 systematic review and meta-analysis by Pizzol et al summarized the impact of cancer treatment on ejaculatory dysfunction across all males with cancer in cross-sectional and case-control studies [ 47 ]. This review established that cancer treatment involving the lower spinal cord can impact ejaculatory function (prevalence of 6.8 to 68.7%).…”
Section: Discussionmentioning
confidence: 99%
“…B. Pizzol et al 2021 ; Santos Gonçalves et al 2022 ), könnte aber durch differenziertere statistische Analysen ergänzt werden. Weiterhin ist zu konstatieren, dass die bisherige Literatur zur Orgasmus-Lücke sich auf cis-geschlechtliche Frauen beschränkt und Aussagen über trans Frauen somit (noch) nicht möglich sind ( Hamm und Nieder 2021 ).…”
Section: Diskussionunclassified